Gertie's ultimate dress book : a modern guide to sewing fabulous vintage styles - Hirsch, Gretchen, 1979- (STC Craft/Stewart, Tabori & Chang, an imprint of ABRAMS, 2016)
Every vintage-obsessed sewist dreams of having a closet full of gorgeous dresses. The follow-up to the popular Gertie's New Book for Better Sewing and Gertie Sews Vintage Casual, Gertie's Ultimate Dress Book is packed with all the information and patterns you could ever need to create a wardrobe filled with stunning vintage frocks. The book begins with all the essential techniques for dressmaking and includes instructions and patterns for 23 dresses for a variety of occasions. Elements of each pattern can be mixed and matched, allowing readers to customise the bodice, skirt, sleeves, pockets and details of each dress for a truly unique creation.